Demonstration of treatment planning software for hyperthermic intraperitoneal chemotherapy in a rat model. (1st January 2021) - Löke, Daan R.; Helderman, Roxan F. C. P. A.; Rodermond, Hans M.; Tanis, Pieter J.; Streekstra, Geert J.; Franken, Nicolaas A. P.; Oei, Arlene L.; Crezee, Johannes; Kok, H. Petra
Abstract: Background: Hyperthermic intraperitoneal chemotherapy (HIPEC) is administered to treat residual microscopic disease after cytoreductive surgery (CRS). During HIPEC, fluid (41–43 °C) is administered and drained through a limited number of catheters, risking thermal and drug heterogeneities within the abdominal cavity that might reduce effectiveness. Treatment planning software provides a unique tool for optimizing treatment delivery. This study aimed to investigate the influence of treatment-specific parameters on the thermal and drug homogeneity in the peritoneal cavity in a computed tomography based rat model. Method: We developed computational fluid dynamics (CFD) software simulating the dynamic flow, temperature and drug distribution during oxaliplatin based HIPEC. The influence of location and number of catheters, flow alternations and flow rates on peritoneal temperature and drug distribution were determined. The software was validated using data from experimental rat HIPEC studies. Results: The predicted core temperature and systemic oxaliplatin concentration were comparable to the values found in literature. Adequate placement of catheters, additional inflow catheters and higher flow rates reduced intraperitoneal temperature spatial variation by −1.4 °C, −2.3 °C and −1.2 °C, respectively. Flow alternations resulted in higher temperatures (up to +1.5 °C) over the peritoneal surface. Higher flow rates also reduced the spatial variation of chemotherapy concentration over the peritoneal surface resulting in a more homogeneous effective treatment dose. Conclusion: The presented treatment planning software provides unique insights in the dynamics during HIPEC, which enables optimization of treatment-specific parameters and provides an excellent basis for HIPEC treatment planning in human applications.